Pengembangan Aplikasi Visualisasi Grafik Sentimen Chat Customer dI PT Dewata Telematika - Anak Agung Istri Intan Permata Sari; I Ketut Gede Suhartana; Ngurah Agus Sanjaya ER (Jurnal Pengabdian Informatika, 2026)
The development of the Customer Chat Sentiment Graphic Visualization Application aims to help PT Dewata Telematics analyze and group sentiment from customer messages that come in via WhatsApp bot. Application development methods include designing a WhatsApp bot as a communication interface, dataset preparation, which includes storing messages in a database, data preprocessing to clean text, sentiment analysis to categorize messages into positive, negative, and neutral, as well as implementing website-based graphic visualization. The development of this application produces an integrated system consisting of a WhatsApp bot for automatic data collection and a website application that visualizes sentiment in the form of line charts, pie charts and bar charts. Implementing this application allows companies to monitor customer satisfaction, evaluate service performance, and respond to complaints more effectively, thereby contributing to increased customer loyalty.